In vivo biocompatibility testing of nanoparticle-functionalized alginate–chitosan scaffolds for tissue engineering applications - Viveros-Moreno, Nancy G.; Garcia-Lorenzana, Mario; Peña-Mercado, Eduardo; García-Sanmartín, Josune; Narro-Íñiguez, Judit; Salazar-García, Marcela; Huerta-Yepez, Sara; Sanchez-Gomez, Concepción; Martínez, Alfredo; Beltran-Vargas, Nohra E. (Frontiers in Bioengineering and Biotechnology, 2023)
Background: There is a strong interest in designing new scaffolds for their potential application in tissue engineering and regenerative medicine. The incorporation of functionalization molecules can lead to the enhancement of scaffold properties, resulting in variations in scaffold compatibility. Therefore, the efficacy of the therapy could be compromised by the foreign body reaction triggered after implantation. Methods: In this study, the biocompatibilities of three scaffolds made from an alginate-chitosan combination and functionalized with gold nanoparticles (AuNp) and alginatecoated gold nanoparticles (AuNp+Alg) were evaluated in a subcutaneous implantation model in Wistar rats. Scaffolds and surrounding tissue were collected at 4-, 7-and 25-days postimplantation and processed for histological analysis and quantification of the expression of genes involved in angiogenesis, macrophage profile, and proinflammatory (IL-1β and TNFα) and anti-inflammatory (IL-4 and IL-10) cytokines. Results: Histological analysis showed a characteristic foreign body response that resolved 25 days postimplantation. The intensity of the reaction assessed through capsule thickness was similar among groups. Functionalizing the device with AuNp and AuNp+Alg decreased the expression of markers associated with cell death by apoptosis and polymorphonuclear leukocyte recruitment, suggesting increased compatibility with the host tissue. Similarly, the Eliminó: í 2 This is a provisional file, not the final typeset article formation of many foreign body giant cells was prevented. Finally, an increased detection of alpha smooth muscle actin was observed, showing the angiogenic properties of the elaborated scaffolds. Conclusion: Our results show that the proposed scaffolds have improved biocompatibility and exhibit promising potential as biomaterials for elaborating tissue engineering constructs.